2015
DOI: 10.3390/ijms161226211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guibi-Tang, a Traditional Herbal Formula, on Retinal Neovascularization in a Mouse Model of Proliferative Retinopathy

Abstract: Ocular pathologic angiogenesis is an important causative risk factor of blindness in retinopathy of prematurity, proliferative diabetic retinopathy, and neovascular macular degeneration. Guibi-tang (GBT) is a frequently used oriental herbal formula in East Asian countries, and is also called Qui-pi-tang in Chinese and Kihi-To in Japanese. In the present study, we investigated the preventive effect of GBT on retinal pathogenic neovascularization in a mouse model of oxygen-induced retinopathy (OIR). C57BL/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Fourth, Qui Pi Tang can be used to treat amnesia, fatigue, poor memory or forgetfulness, anorexia, anemia, insomnia, palpitation, and neurosis [27]. It can also treat blood stools, Evidence-Based Complementary and Alternative Medicine subcutaneous purple spots, diet reduction, pain, and severe insomnia [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, Qui Pi Tang can be used to treat amnesia, fatigue, poor memory or forgetfulness, anorexia, anemia, insomnia, palpitation, and neurosis [27]. It can also treat blood stools, Evidence-Based Complementary and Alternative Medicine subcutaneous purple spots, diet reduction, pain, and severe insomnia [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…One of the major ingredient in GBT is decursin, which inhibited retinal neovascularization in a mouse model of retinopathy in prematurity [ 37 ]. Irrespective of the effects of GBT, information on its underlying mechanisms during retinal neovascularization is limited [ 107 ]. Lee and associates examined the effect of GBT on pathogenic retinal neovascularization in a mouse model of oxygen-induced retinopathy.…”
Section: Recent Evidences Of Traditional Medicinal Plants In Diabementioning
confidence: 99%
“…Intraperitoneal administration of GBT (50 or 100 mg/kg/day) in OIR C57BL/6 mice significantly reduced pathogenic angiogenesis of the retina, and the protein level of plasminogen activator inhibitor-I. Real-time PCR demonstrated that GBT lowered mRNA levels of VEGF, fibroblast growth factor-2, and plasminogen activator inhibitor-1 in OIR mice [ 107 ]. Therefore, GBT exerts anti-angiogenic effects through partial inhibition of fibroblast growth factor-2, plasminogen activator inhibitor-1 and VEGF.…”
Section: Recent Evidences Of Traditional Medicinal Plants In Diabementioning
confidence: 99%
“…Water extract of guibi-tang (GB), a traditional herbal formula, is a mixture of 12 herbs and is known as Qui-Pi-tang in Chinese and Kihi-To in Japanese. [ 13 14 ]. GB has been traditionally used to treat amnesia, fatigue, insomnia, anemia, and palpitations [ 15 ].…”
mentioning
confidence: 99%
“…Studies have shown that GB has various pharmacological activities, including immunoregulatory, antioxidant, and gastroprotective effects. GB inhibits ischemic retinal angiogenesis by suppressing VEGF and PAI-1 expression and exhibits apoptotic activity by regulating mitogenactivated protein kinases (MAPKs) [ 13 16 ]. However, thus far, no studies have reported the protective effects of GB against pulmonary inflammation induced by CS and lipopolysaccharide (LPS).…”
mentioning
confidence: 99%